Natural Capital Accounting : Informing Policy Decisions and Management of Uganda’s Natural Resources - World Bank (World Bank, Washington, DC, 2020)
The Government of Uganda has been working to establish a new system of NCA. NCA is a standardized approach to measuring and valuing natural resources. It overcomes the limitations of traditional economic measurements, such as gross domestic product (GDP), that look primarily at income and not at wealth. It provides physical and monetary information about natural capital wealth as well as income and other benefit flows. As such,NCA is already helping to inform key policies and plans in Uganda. The development of NCA in Uganda has been supported by various development partners, notably the World Bank’s global program, WAVES. This paper offers an independent synthesis of Uganda’s work with WAVES from 2018 to 2020. It is based on program documentation and a review of the accounts themselves, supplemented by interviews of key Ugandan officials involved in the process.